Transvaginal Ultrasound Assessment of Cervical Length in Threatened Preterm Labor - Prasila Ekaputri (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objectives: To determine the cut off point of cervical length usingtransvaginal ultrasonography to predict the actual occurrence ofpreterm labor in women with threatened preterm labor. Methods: A cross sectional study with consecutive random samplingmethod. We examined 80 women with singleton pregnancycomplaining of regular, painful uterine contraction and rupturedmembrane at 24-36 weeks of gestation. Women in active labor, definedby the presence of cervical dilatation less than or equal 3 cm, and having complicationwere excluded. When the patient was admitted, a transvaginalscan was performed to measure the cervical length. Parenteralmagnesium sulfate was given as the subsequent management.The primary outcome was delivery within 24 hours of presentation.Results: We found that the optimal cut off values for cervical lengthwas 2.65 cm with sensitivity 94.4 Percent, specificity 65.4Percent, positive predictivevalue 75.4 Percent and negative predictive value 81.8 Percent. In 69cases, the cervical length was more than or 2.65 cm, with 52 patients successfullycontinued their pregnancy until more than 24 hours. In the 11cases with cervical length less than or equal 2.65 cm, delivery within 24 hours occurredin 9 cases (81,8 Percent). Conclusion: The findings of this study suggest that in women withthreatened preterm labor, cervical length more than or equal 2.65 cm may help predictthe actual occurrence of preterm labor. Keywords: cervical length, threatened preterm labor, transvaginalultrasonography